Nesting ecology of East Pacific green turtles at Playa Cabuyal, Gulf of Papagayo, Costa Rica - Santidrián Tomillo, Pilar (2014)
East Pacific green turtles (Chelonia mydas), often referred to as black turtles, are smaller and exhibit a lower reproductive output than other populations of green turtles in the Atlantic, Indian and Western Pacific Oceans. Knowledge of nesting ecology of East Pacific green turtles is limited to general descriptions. We conducted an exhaustive analysis of the nesting ecology of East Pacific green turtles at Playa Cabuyal, North Pacific Costa Rica. Compared with other populations of green turtles, East Pacific turtles exhibited smaller clutch sizes (mean ± SD: 76.9 ± 18.2 eggs per clutch), but the number of clutches (estimated clutch frequency (ECF): 4.3 ± 2.3 clutches) fell within the upper limit reported for green turtles. Clutch size and seasonal reproductive output (409 ± 135 eggs per female), but not ECF, increased with female size. The observed internesting period (OIP) between consecutive oviposition events (mean ± SD: 15.4 ± 2.9 days) increased as the season progressed and was approximately 2 days longer than the mean OIP reported for the species. Most clutches were laid in the upper vegetated part of beach (zone 3, 75%) and within this zone, tended to be located underneath trees (79%). Hatching success of clutches laid underneath trees was significantly higher (0.89 ± 0.17) than that of clutches laid in the exposed areas of zone 3 (0.75 ± 0.33). Mean duration of the nesting process (3:14 h) was on average 45 min longer than previously reported for the species. Frequency of false crawls was high (49% of nesting activities), and nesting success was low (54% of nesting attempts). Poaching of eggs, tourism and predation by dogs were important threats to this population. Conservation actions were being successfully implemented at the local level due to presence of beach patrollers, but official protection is needed for the preservation of the nesting population into the future.